Air‐interface virtualization using filter bank multicarrier and orthogonal frequency division multiplexing configurations. Issue 2 (23rd October 2020) - Saad, Malik Muhammad; Bhatti, Farrukh Aziz; Zafar, Adnan; Jangsher, Sobia; Kim, Dongkyun; Maqsood, Moazam
Abstract: Mobile networks have to cater for diverse services that have distinct requirements in terms of bandwidth, latency, and so on. Network virtualization is a key technology that efficiently utilizes the network resources to meet these service requirements. In this work, we investigate radio virtualization for creating fine‐grained network slices using orthogonal frequency division multiplexing (OFDM) and filter bank multicarrier (FBMC) combinations; the two are individually referred to as virtual radios (VRs). Using universal software radio peripherals (USRPs), we experimentally analyze multiple configurations of VRs including OFDM‐OFDM, OFDM‐FBMC, and FBMC‐FBMC. An extensive performance comparison is done on the basis of error rate, spectral efficiency, interference power, and computational complexity of the VR configurations that are confined within an operational bandwidth. An increase in transmit power of the VRs is theoretically expected to decrease the error rate, but there is also an increase in adjacent channel interference. Therefore, after a certain decrease in error rate with increase in transmit power, an inflection point is reached after which the error rate starts to increase. Of the three combinations, FBMC‐FBMC gives the lowest error rate (at the highest transmit power), that is, 10% and 18% lower than OFDM‐FBMC and OFDM‐OFDM, respectively. However, FBMC‐FBMC also has the highest complexity. We conclude that this air‐interface virtualization framework allows the network to use the waveform configuration that is best suited to a particular set of services, while considering the pros and cons of the individual waveforms. Abstract : This article experimentally investigates radio virtualization using FBMC and OFDM air‐interfaces. The performance of the virtual radios is analyzed while focusing on the issues that arise in the radio domain, e.g., interference. This air‐interface virtualization framework allows the network to use the waveform configuration that is best suited to a particular set of services.